Development of extensional fault and fold system: Insights from 3D seismic interpretation of the Enderby Terrace, NW Shelf of Australia. (June 2019) - Deng, Hongdan; McClay, Ken
Abstract: Extensional fault-related folding has been widely observed in rift systems that are characterised by basement-involved fault reactivation. On the Enderby Terrace, NW Shelf of Australia, oblique reactivation of a basement structure resulted in a depth-branched fault system that consists of six splay faults in the cover stratigraphy. Extensional fault-related folding is obvious and predominantly developed in the hangingwall of reactivated basement fault. The mechanically weak Locker Shale not only plays an important role in displacement accommodation at the basement fault tip but also exerts a strong impact on 'flat' development of the 'ramp–flat–ramp' fault, thereby controlling the location and geometry of the hangingwall anticline. The kinematic evolution of these structures can be determined based on the well-preserved stratigraphy of the hangingwall basins. Faults and folds deformation exhibits systematic lateral changes which provides clues for the kinematic evolution of the hangingwall folds, that is (i) hangingwall synclines and anticlines formed as a result of fault propagation and linkage, (ii) partial truncation of the anticline by adjacent fault segments due to lateral fault lengthening and interaction, and (iii) complete truncation of the anticline by a planar fault that results in the abandonment of the curved fault plane in the footwall. Results of this study are applicable to other extensional fault and fold systems of similar origin and provide models for partially preserved outcrop deformation and poorly imaged seismic data interpretation. Highlights: The structural style is a basement fault that systematically branches upward into fault splays, with fault-parallel anticline and syncline deformations predominantly occurred in the hangingwall. Fault displacement decreases upward and fault-fold activation timing is documented by stratigraphic architecture in the hangingwall basins. Numerical modelling of the fault geometrical evolution was conducted to validate the interpreted deformation process, and comparison and contrast with existing models provide guideline for better assessment of the evolution process and controlling factors of the fault-fold system. 3D fault-fold architecture demonstrates the geometrical and kinematic relationship of fault and fold.